การธำรงรักษาบุคลากรด้านแรงงานในอุตสาหกรรมสิ่งทอและเครื่องนุ่งห่ม - อุ่นแสงจันทร์ คณิศร; พันธุ์พานิช นพดล (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: This research aimed to study the causes of resignation of employees and its impacts in order to propose guidelines for retention of labor personnel in the textile and apparel industry. METHODS: Mixed method approach by in-depth interviews and group discussion with 19 key informants and sample survey of 50 respondents in the textile and apparel industry. RESULTS: The textile and apparel industry employed foreign workers to replace Thai workers because Thai workers resigned from work, entrepreneurs changed to more machines, wages were low, and workers preferred easier work. CONCLUSIONS: The organizations were strongly advised to pay more attention to the retaining of personnel with effective management of human resources, particularly employment security, sufficient corporate support, and persistence engagement of the workforce in management and the organizations.